Caracterização das amostras clínicas de Cryptococcus neoformans isolados no estado de Sergipe no período de 2001 a 2004 - Barbosa Junior, Antonio Marcio (2005)
Cryptococcus neoformans is one yeast opportunist that it unchains meningitis in imunocompetentes patients in such a way as in patients This work had as objective to study the varieties (neoformans and gattii) of isolated C.neoformans in the State of Sergipe from the liquor liquid of patients with infectious miningitis. Also had as objective to determine the sensitivity of C. neoformans variety neoformans and variety gattii, isolated of the líquor of patients with infectious meningite in the State of Sergipe, through the microdilution method (NCCLS) and to determine the sexual type - mating type of isolated physicians of Cryptococcus neoformans through the Reaction in Chain of DNA Polimerase (PCR) in Sergipe. Samples of the LCR had been used that had given entered in the IPH/LACEN/SE in the period of 2001 the 2004. Direct microscopy through the coloration with Nanquim Ink was carried through. An aliquot one of the líquor (0,1mL) was transferred to pipes contends Agar Sabouraud with clorafenicol and incubado in ambient temperature 25ºC and 37ºC. Tests for presumptive, fenotípica identification had been carried through in half Níger and of the varieties in half CGB. In the analyzed period, only one sample presented fenotípicas characteristics in half Níger differentiated of the others. Of the total of 15 samples analyzed in half CGB, 02 samples (13,33%) if had presented positive, or either, had been identified as variety gattii, being one of them isolated one of soronegativo patient for HIV (patient not aidético). The others 13 samples (86,67%) had presented negative CGB, or either, they had been identified as variety neoformans. The majority of the isolated samples of Cryptococcus neoformans of the líquor of patients with infectious meningite is of the variety neoformans in Sergipe. For the accomplishment of the sensitivity test variety had been used two samples of C. neoformans var. gattii and 11 of C. neoformans listed variety neoformans above. For control of the tests standard ATCC 32608 was used. After that suspension of fúngicas cells. The following antifungal had been used: Anphotericin B, Fluconazol, Cetoconazol, Miconazol, Itraconazol, 5- Fluorocitosina and Terbinafrina. The fungal suspension was adjusted in a final concentration of 0,5x10³ for 2,5x10³ UFC in the half RPMI. The experiment was carried through in microtitulação plates. After the inoculation, the microdilution plates had been incubadas 37ºC and deal in 24, 48 and 72 hours. The end point of the CIM was determined in the readings of 48 and 72 hours. The isolated physicians of C. neoformans had presented high values of CIM for the antifungal agents tested, what he mainly symbolizes one high tax of resistance Anfotericina B and to the Fluconazol, given that he can be correlated with the clinical data. For analysis of mating type sexual of C. neoformans from the líquor of patients with infectious meningite in Sergipe during the period of 2001 and 2004 had been used 13 samples. The related laboratoriais procedures to molecular biology (extration of DNA and accomplishment of the PCR) had followed as Chatuverdi reference et al. (2000). All the samples of C.neoformans tested, as much that pertaining to the variety neoformans as gattii are matting type, considered of bigger virulence.